Optimasi Pemakaian Sendiri PLTU dengan Metode Audit Energi pada Motor Listrik 3 Fasa di PLTU X - Rio Afrianda; Samsurizal Samsurizal (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2020)
PLTU X is an industrial power plant with a large consumption of electrical energy for its own use. In ISO50001, every industry with a large Energy Consumption Intensity (IKE) needs to be audited for energy consumption. The company performance contract also regulates that the percentage of own use should not exceed 6% of electricity production. Currently, the percentage of own use in PLTU X unit 5 is greater than unit 4. For this reason, it is necessary to conduct an energy audit for own use with the aim of reducing the percentage of own use in unit 5 by 0.5% from current conditions and finding opportunities for energy savings at PLTU X unit 5. To analyze this problem using the energy audit method, analysis using the performance test method using the